N‐Methyl‐d‐Aspartate Receptor Antagonism has Differential Effects on Alcohol Craving and Drinking in Heavy Drinkers. (9th February 2015) - Krishnan‐Sarin, Suchitra; O'Malley, Stephanie S.; Franco, Nicholas; Cavallo, Dana A.; Morean, Meghan; Shi, Julia; Pittman, Brian; Krystal, John H.
Abstract : Background: The objective of this study was to determine the effects of the N ‐methyl‐d ‐aspartate (NMDA) receptor antagonist, memantine (0, 20, 40 mg/d), upon alcohol drinking and craving in heavy drinkers with or without a family history (FH) of alcoholism, and to explore the modulatory influence of the presence of impulsivity on these outcomes. Methods: Ninety‐two, nontreatment‐seeking, heavy drinkers received memantine or placebo for 8 days. On the eighth day, they received a priming dose of alcohol followed by a 3‐hour period of alcohol access. Results: Memantine at a dose of 20 mg reduced alcohol craving but did not influence alcohol drinking. No effects of FH were observed. In participants with higher baseline levels of impulsivity, 40 mg of memantine reduced alcohol craving but increased alcohol drinking and alcohol‐induced stimulation. Conclusions: NMDA receptor signaling may play divergent roles in mediating alcohol cue‐induced craving and alcohol drinking in heavy drinkers. The potential efficacy of memantine as monotherapy for alcohol use disorders may be limited by its tendency to disinhibit drinking in some individuals.